The role of heme oxygenase-1 (HO-1) in the regulation of inflammatory reaction, neuronal cell proliferation and apoptosis in rats after intracerebral hemorrhage (ICH) - Fan XZ (Neuropsychiatric Disease and Treatment, 2016)
Xuezheng Fan,1 Linshen Mu2 1Department of Neurosurgery, People’s Hospital of Guangming New District, Shenzhen, Guangdong, People’s Republic of China; 2Department of Neurosurgery, Guangzhou Medical University Affiliated Brain Hospital, Guangzhou, Guangdong, People’s Republic of China Objective: To investigate the role of heme oxygenase-1 (HO-1) in the regulation of inflammatory reaction, neuronal cell proliferation and apoptosis in rats after intracerebral hemorrhage (ICH).Methods: Thirty-six adult Sprague Dawley (SD) male rats were randomly divided into sham operation, ICH and zinc protoporphyrin (ZPP) group. Rats (except for the sham operation group) were given 50 µL stereotactic injection of autologous blood from the femoral artery into the caudate nucleus, to establish an ICH model. In addition, rats in the ZPP group were given 10 mg/kg intraperitoneal injection of ZPP. At day 3 postoperative, neurobehavioral changes and brain water content were evaluated, brain tissue HO-1 expression was detected with immunohistochemistry and reverse transcription polymerase chain reaction (RT-PCR), brain tissue apoptosis was evaluated with TUNEL method, Caspase 3, Caspase 8 and Caspase 9 activity were detected with colorimetric method, level of TNF-α, IL-1β, IL-6 and IL-8 were measured with the enzyme-linked immunosorbent assay (ELISA), while Bcl-2, Bax, p-NF-κB p65 and p-IκBα protein expression were detected with Western blot.Results: ICH group compared to sham operation: HO-1 positive rate and mRNA expression were increased, neurological deficit score and cell apoptosis rate were increased, Caspase 3, Caspase 8 and Caspase 9 activity were increased, level of TNF-α, IL-1β, IL-6 and IL-8 were increased, Bcl-2 expression was downregulated, Bax, p-NF-κB p65 and p-IκBβ expression were upregulated. The differences were statistically significant (P<0.01). ZPP group compared to ICH: HO-1 positive rate and mRNA expression were decreased, neurological deficit score and cell apoptosis rate were decreased, Caspase 3, Caspase 8, Caspase 9 activity were decreased, level of TNF-α, IL-1β, IL-6 and IL-8 were decreased, Bcl-2 expression was upregulated, Bax, p-NF-κB p65 and p-IκBα expression were downregulated, and the differences were statistically significant (P<0.01).Conclusion: HO-1 inhibitor, ZPP does have a protective effect on ICH rats. This might be due to its inhibition to the inflammatory reaction and neuronal cell apoptosis. Keywords: heme oxygenase-1, intracerebral hemorrhage, inflammatory reaction, apoptosis